The Motif of the ‘Mirror’ in Literary Works (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Mirrors have always been thought of as enigmatic objects. It has the enchanted ability to foretell the future. It acts as a doorway or portal connecting the other world to this one. Additionally, it symbolizes an individual's unconsciously held alter ego, spirit, shadow, or other identity. As a result, it has also been perceived as a source of terror. The motif of the "mirror" in literary works, along with the pictures and ideas it carries, will be thoroughly examined in this paper.